Historiography on the “Siberian” Period of Mikhail Bakunin (1857-1861): A Critical Discourse - Dolzhikov, Vyacheslav A. (Journal of History Culture and Art Research, 2019)
The paper critically reviews the available scientific and biographical literature, which examines the four-year period of social activity of the Russian thinker and opposition politician Mikhail Bakunin in Siberia during the “thaw” of the late 1850s and early 1860s. The purpose of the study is to provide critical perspectives on the myths of historiography that interfere with the reconstruction of Mr. Bakunin’s “Siberian period.” Thus, the author of the article aims to achieve the restoration of Mikhail Bakunin’s place and role in the public life of Russia in those times. In particular, the author refutes the myth that the “great rebel” was allegedly in a voluntary self-isolation during that period of his life. In addition, the dubious source of this historiographical version is critically analyzed, dating back to Mikhail Katkov, a very famous ideologist of imperial conservatism. The author argues that the Katkov’s legend turned into a toolbox of official communist historiography, and then it was reproduced virtually unchanged in publications of the Soviet era until the collapse of the dominant regime. First of all, the author proposes to radically rethink the false conception of the "Siberian" period of Mikhail Bakunin that has become entrenched in historical literature. Second, the author considers it necessary to justify the redirection of the copyright affiliation of some sources of radical revolutionary journalism in 1860-1861 to Mikhail Bakunin, including the famous "Letters" (1860) to the editorial office of the Russian emigrant newspaper "The Bell." Based on the methodology of textual content analysis of the keywords inherent in this journalistic message and similar letters from Mr. Bakunin from Siberia, the author formulates the main conclusion: the real author of this appeal at that moment could be only the closest friend and associate of Alexander Herzen, i.e., Mr. Bakunin himself.